Flotation separation of scheelite from calcite using pectin as depressant. (1st June 2019) - Jiao, Fen; Dong, Liuyang; Qin, Wenqing; Liu, Wei; Hu, Chenqiang
Highlights: Flotation separation of scheelite from calcite is difficult. Pectin can chemically adsorb on calcite surface. Flotation separation of scheelite from calcite can be achieved with pectin. An adsorption model and separation model are finally obtained. Abstract: In this paper, pectin, a polymer polysaccharide, was studied for its depression during the selective flotation separation of scheelite from calcite. Zeta potential experiment, FTIR analysis and XPS analysis were used to explain the selective depression mechanism of pectin on the two minerals. The microflotation experiment showed that the pectin had a strong depressive effect on the calcite, but had little effect on the floatability of the scheelite in the pH range of 7–9. The flotation recovery of calcite dropped sharply to 4.56%, while scheelite still maintained a high flotation recovery of 71.01% at pH 7.5. A series of mechanism experiments showed that the localized ions on the surface of scheelite and calcite were mainly tungstate and calcium species, and the dominant component on the calcite surface was mainly positively charged calcium species. The carboxyl groups on the pectin molecular chains can be chemically chelated with the calcium species on the calcite surface and adsorbed on the calcite surface. The large amount of adsorption of pectin hindered the further adsorption of the collector sodium oleate (NaOL) on calcite surface, thereby greatly reducing the floatability of calcite, and finally achieving the flotation separation of the two minerals. Finally, the adsorption model of pectin and the separation model between the two minerals can be obtained.